ACCULTURATION OF ISLAMIC CULTURE AND SAYYANG PATTU’DU AT DESA LERO, DISTRICT SUPPA, REGENCY PINRANG - Musyarif, Musyarif; Ahdar, Ahdar; Multazam, Multazam (Jurnal Diskursus Islam, 2020)
The tradition of sayyang pattu'du is the ancestral culture of Mandar which is combined with Islamic culture, as a form of appreciation to the children who love the Qur'an, so it becomes a motivation for children to immediately attend the Qur'an. The sub-problems in this study, namely 1) How the beginning of the emergence of the tradition of Sayyang Pattu'du, 2) How is the procedure for implementing the tradition of Sayyang Pattu'du in the village of Lero, 3) How is the acculturation of Islam with the tradition of Sayyang Pattu'du. and the purpose of this research is to find out the beginning of the emergence of the tradition of Sayyang Pattu'du in the village of Lero. This type of research is descriptive qualitative research using data collection techniques namely observation, interviews, and documentation. The approach used is historical approach, sociology, anthropology, phenomenology and theology. Data analysis techniques used are deductive, inductive and comparative. The results showed that: the beginning of the emergence of the tradition of sayyang pattu'du when Islam entered in the land of Mandar during the reign of the kingdom of Balanipa, namely the fourth king Daetta tommuane, which was under the preachers. Then it was developed by K.H Muhammad Tahir Imam Lapeo, so that this tradition developed and was carried out until in the village of Lero because the majority of the population was the Mandar tribe. In the village of Lero, the implementation of the sayyang pattu'du tradition was carried out every two years coupled with the birthday of the Prophet Muhammad. The procedure for implementing it is through several stages, namely first preparing the things needed, ma'barasanji, marrattas baca and parrawana. This tradition is an acculturation of Islam and the culture of Mandar ancestral ancestors. The acculturation of Islam and the culture of the ancestors of the mandar found in the tradition of sayyang pattu'du are khatam al-Qur'an, the birthday of the Prophet Muhammad, reading of barzanji, traditional customs of Mandar, Mandar art (rawana and kalinda'da), motivating others, and hospitality